(untitled) (ENTHYMEMA International journal of literary criticism, literary theory, and philosophy of literature, 2019)
This paper sets out to re-approach the famous leptêacrostich in Aratus’ Phaenomena (783-87) by confronting it with other early Greek acrostichs and the discourse of technê and sophia,which has been shown to play an important role in a gamut of Greek literary texts, including texts very much relevant for the study of Aratus’ acrostich. In particular, there is a tantalizing connection between the acrostich in Aratus’ poem that poeticized Eudoxus’ astronomical work and the so-called Ars Eudoxi, a (pseudo-)Eudoxian acrostich sphragisfrom a second-century BC papyrus.